REFORMS IMPLEMENTED IN THE SECONDARY SPECIALIZED AND VOCATIONAL EDUCATION SYSTEM OF UZBEKISTAN (2017-2021) - Ne’matov Sh. U. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the reforms and changes implemented in the secondary specialized and vocational education system of the Republic of Uzbekistan based on the Action Strategy. Furthermore, it provides a statistical analysis of changes related to: the normative-legal documents and state programs adopted in the sector between 2017-2021, the execution of these programs, the financial condition of educational institutions; their material-technical base, and the operational activities of these institutions.